2021
DOI: 10.1016/s2589-7500(21)00131-x
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of COVID-19 in the UK using self-reported symptoms: a large-scale, prospective, epidemiological surveillance study

Abstract: Background Self-reported symptoms during the COVID-19 pandemic have been used to train artificial intelligence models to identify possible infection foci. To date, these models have only considered the culmination or peak of symptoms, which is not suitable for the early detection of infection. We aimed to estimate the probability of an individual being infected with SARS-CoV-2 on the basis of early self-reported symptoms to enable timely self-isolation and urgent testing. MethodsIn this large-scale, prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 30 publications
2
51
0
1
Order By: Relevance
“…REACT also suggested having different symptom sets for adults and children in order to optimise sensitivity, which would require careful public health messaging. ZOE [8] suggested an algorithm also including working in healthcare; whilst this could theoretically be programmed into an online test system, such complexity risks gaming the system if individuals cannot otherwise get a test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…REACT also suggested having different symptom sets for adults and children in order to optimise sensitivity, which would require careful public health messaging. ZOE [8] suggested an algorithm also including working in healthcare; whilst this could theoretically be programmed into an online test system, such complexity risks gaming the system if individuals cannot otherwise get a test.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have restricted to those hospitalised or seeking healthcare, who do not represent most infections [6]. Three recent UK community-based studies suggested that sensitivity could be increased by 10-20% by extending the "classic" symptoms (REACT [7], adding combinations of headache, muscle aches, chills and appetite loss depending on age; ZOE [8], adding different symptoms depending on age, sex, BMI and working in healthcare; VirusWatch [9], adding feeling feverish, headache, muscle aches, loss of appetite or chills) but at a cost of increasing numbers eligible for testing 2-3 fold and tests per positive identified up to 7-fold. However, these studies were mainly before widespread vaccination, and whilst Alpha dominated.…”
Section: Introductionmentioning
confidence: 99%
“…To date there have been relatively few other reported studies of COVID-19 symptoms, and even fewer reporting their use to inform public health actions or clinical decision making [ 4 7 , 9 , 10 , 29 , 30 ]. A study using data from the UK Covid Symptom Smartphone Application used a similar approach to the New Zealand study, combining symptom data with demographic information to predict COVID-19 PCR test positivity [ 6 ]. Models were trained using data collected at several time points and showed a similar level of prediction of test positivity to the New Zealand random forest model (AUC ~ 0.8).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have described the use of self-reported symptoms to develop and train models that can identify infection, with the aim of identifying cases early in the course of infection, enabling prompt self-isolation and testing [ 4 6 ]. These include the use of large datasets of self-reported symptoms and PCR test results, collected via mobile phone applications, and an array of modelling methods including logistic regression [ 4 , 5 ] and a hierarchical Gaussian process model [ 6 ] and machine learning models [ 7 , 8 ]. Self-reported symptoms have also been used to identify changes in the symptomatology and disease profiles associated with vaccination [ 9 ] and the introduction of new variants of concern [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported symptoms during the COVID-19 pandemic have been used to train AI-based models to identify possible COVID-19 infection. Although studies based on early self-reported symptoms, such as [ 23 , 24 ], are widely used for identifying COVID-19 cases, no validated tool exists for surveying COVID-19 infection in the general population. Indeed, COVID-19 data are gathered in many countries to understand the pandemic and be prepared for the future.…”
Section: Literature Review Background and Motivationmentioning
confidence: 99%